NEW INSIGHTS INTO THE THIAZOLIDINEDIONES AS AN ADD-ON THERAPY TO METFORMIN AND GLIMEPIRIDE IN PATIENTS WITH UNCONTROLLED TYPE 2 DIABETES MELLITUS - ABBAS, MA; ULLAH, H; ARBAB, M; LAGHARI, AS; HAQ, UU; ABBAS, Q; AHMED, B (Biological and Clinical Sciences Research Journal, 2024)
Diabetes mellitus is a complex metabolic disorder that requires multifaceted management, including frequent blood glucose monitoring, polypharmacy, and timely therapeutic adjustments. Thiazolidinediones have been proposed as an effective add-on therapy to existing regimens to improve glycemic control in patients with Type 2 Diabetes Mellitus (T2DM). Objective: To evaluate the effectiveness of Thiazolidinediones as add-on therapy in diabetic patients already taking metformin and glimepiride. Methods: This observational, comparative, and follow-up cohort study was conducted in a tertiary care hospital in Pakistan. A total of 90 patients with poorly controlled T2DM were enrolled and randomly divided into two groups: Group A (n=45) received standard oral therapy with metformin and glimepiride, while Group B (n=45) received metformin, glimepiride, and Thiazolidinediones. The study outcomes included changes in Hemoglobin A1c (HbA1c), fasting blood sugar (FBS), and body mass index (BMI) throughout the study. Statistical analyses were performed using appropriate methods, with significance at p < 0.05. Results: The addition of Thiazolidinediones in Group B resulted in superior glycemic control compared to Group A. Group B exhibited a 16.1% reduction in HbA1c versus an 8.2% reduction in Group A (p < 0.05). FBS levels decreased by 28.8% in Group B compared to a 14.6% decrease in Group A (p < 0.05). Additionally, BMI decreased by 1.5% in Group B, whereas Group A showed a slight increase of 0.06% (p < 0.05). Significantly, the addition of Thiazolidinediones did not exacerbate the toxicity of the existing drug regimen. Conclusion: The study demonstrates that Thiazolidinediones, when added to standard therapy with metformin and glimepiride, offer significant improvements in glycemic control without additional toxicity. This combination therapy may be a beneficial strategy for managing poorly controlled Type 2 diabetes mellitus in the Pakistani population.